2022
DOI: 10.1093/rheumatology/keac359
|View full text |Cite
|
Sign up to set email alerts
|

Activation of circulating monocytes by low-density lipoprotein—a risk factor for osteoarthritis?

Abstract: Synovial macrophages are key mediators of OA pathology, and skewing of macrophage phenotype in favour of an M1-like phenotype is thought to underlie the chronicity of synovial inflammation in OA. Components of the metabolic syndrome (MetS), such as dyslipidaemia, can affect macrophage phenotype and function, which could explain the link between MetS and OA development. Recently published studies have provided novel insights into the different origins and heterogeneity of synovial macrophages. Considering these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…LDL is a cholesterol-rich lipoprotein. Kruisbergen et al found that LDL activation of circulating monocytes was a risk factor for OA 41 ; Oliviero et al found higher levels of serum LDL in patients with OA in comparison to controls 42 ; Mishra et al found higher LDL in the OA group than in the control group 43 . However, the results of this type of study are contrary to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…LDL is a cholesterol-rich lipoprotein. Kruisbergen et al found that LDL activation of circulating monocytes was a risk factor for OA 41 ; Oliviero et al found higher levels of serum LDL in patients with OA in comparison to controls 42 ; Mishra et al found higher LDL in the OA group than in the control group 43 . However, the results of this type of study are contrary to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%